2020
DOI: 10.1152/ajpendo.00302.2019
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of miR-297b-5p protects against stearic acid-induced pancreatic β-cell apoptosis by targeting LATS2

Abstract: Chronic exposure to high concentrations of stearic acid (C18:0) can result in β -cell dysfunction, leading to development of type 2 diabetes. However, the molecular mechanisms underlying the destructive effects of stearic acid on β-cells remain largely unknown. In this study, we aimed to investigate the role of miR-297b-5p on stearic acid-induced β-cell apoptosis. Differential expression of microRNAs (miRNAs) was assessed in a β-TC6 cell line exposed to stearic acid, palmitic acid, or a normal culture medium b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 48 publications
2
38
0
Order By: Relevance
“…Although palmitic and stearic acids may play a differential role in pulmonary disease pathogenesis, increased circulating stearic acid has been shown to cause cardiac and pancreatic β cell lipotoxicity. [39][40][41] We have demonstrated that brominated fatty aldehyde, when administered into the LV, can cause cardiac damage and dysfunction similar to Br 2 inhalation; however, the effects of elevated BFAs need to be investigated. 2 Pulmonary damage as assessed by measuring BALF protein, which is indicative of alveolar-capillary disruption in the lung, correlated with total bromostearic acid contents in cardiopulmonary tissue and plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Although palmitic and stearic acids may play a differential role in pulmonary disease pathogenesis, increased circulating stearic acid has been shown to cause cardiac and pancreatic β cell lipotoxicity. [39][40][41] We have demonstrated that brominated fatty aldehyde, when administered into the LV, can cause cardiac damage and dysfunction similar to Br 2 inhalation; however, the effects of elevated BFAs need to be investigated. 2 Pulmonary damage as assessed by measuring BALF protein, which is indicative of alveolar-capillary disruption in the lung, correlated with total bromostearic acid contents in cardiopulmonary tissue and plasma.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of T2DM has been increasing worldwide, with an estimated 336 million people currently affected [21]. It is well established that exposing pancreatic β cells to an elevated level of stearic acid causes their dysfunction, which is far advanced by the time diabetes is diagnosed clinically [1][2][3]5]. Therefore, the optimal management and prevention of T2DM should aim to ameliorate β-cell dysfunction at an early stage.…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of studies have preliminarily explored the mechanisms underlying stearic acidinduced pancreatic β-cell damage, the exact molecular targets and associated pathways still need to be established. Recently, accumulating evidence has suggested that noncoding RNAs play an important role in the β-cell injury caused by the long-term consumption of a high-fat diet, such as microRNAs [2,5], circRNAs [22,23], and lncRNAs [17,24,25]. Nevertheless, few studies have focused on the role of lncRNAs in β-cell dysfunction upon exposure to elevated levels of SFAs, especially stearic acid, on which no related research has previously been published.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations